Using а neuro-linguistic programming’s classification in the methodology of teaching foreign languages - Пугач, Богдана Валеріївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The work was considering the classification of students Ьу type of perception, information processing and storage, which is used in one of the newest psycho-neuro-linguistic programming. We described three types of modalities of students, as well as the basic forms of construction of the leaming process taking into account the peculiarities of the perception of each group. On the basis of the theoretical material and the results of the study we proved the effectiveness of using NLP strategies in the process of leaming the foreign language.